Dress Fashion Politics of Ghanaian Presidential Inauguration Ceremonies from 1960 to 2017 - Osuanyi Quaicoo Essel (Fashion and Textiles Review)
Presidential inaugurations are statutory in Ghana, but what a president wears during his inauguration are non-statutory, yet, it is a salient visual communicative apparatus that pulls the strings of patriotism, nationalism and fosters a sense of belongingness. In an attempt to throw light on the dress fashion politics of president-elects, the study examined their chronological inaugural dress fashion choice from 1960 to 2017 in order to establish the trend of dress cultural identity they have portrayed during their respective inauguration ceremonies. Using census sampling technique, the sample consisted of all democratically elected Presidents from the first to the fourth Republic. The instrumentation used were motion pictures, archival records and images of the president-elects during their respective inaugural ceremonies. Motion pictures and images gathered were subjected to semiological analysis. The study revealed that seven of the eight president-elects selected their inaugural ceremony dress fashion from the repertoire of Ghanaian fashion classics to signal their Ghanaian dress cultural identity. Their dress fashion, fabric weaves, pattern symbolisms and construal of colours used were sourced from the cultural knowledges of multi-ethnic nationalistic ideological experience and mindset with the aim of fostering unity, nationalism, and display of their Ghanaian identity. Though their ethnic cultural backgrounds and geographical locations partially influenced their dress fashion choice for their inaugural ceremonies, the nationalistic purview and psychologisation of the inauguration atmosphere took precedence, hence the blend in terms of fashion classics and fabric used. The study recommended that parliament must consider making presidential dress fashion choice statutory due to its cultural, social, political and economic factors for the development of textiles and fashion in Ghana.